The construction of a semiotic-pedagogical perspective in arts teacher training (Palíndromo, 2022)
This paper discusses the scope that the development of a semiotic-pedagogical approach in arts teacher training may entail, in attention to the significant dimension of artistic discursivities, the aesthetic dimension of contemporary media discourses and the ways in which both are embedded in the development of the subjectivity of social actors. To this end, the way in which a complex network of intersubjective relationships is configured in the pedagogical meeting and how this emerging space operates as a base matrix for the deployment of a process of deconstruction of social meanings is interrogated. After a journey through different constitutive aspects of the pedagogical field and approaching various features related to the political nature inherent to the educational act, we discuss the way in which attention to the significant dimension of both educational praxis and artistic discourses can lead to the development of a critical and reflective positioning as part of a critical and transformative pedagogy. Finally, by way of conclusion, some challenges and contributions that can make the development of this semiotic-pedagogical perspective in arts teacher training are formulated.
Keywords: Semiotics.; Pedagogy; Arts Teacher Training